Effects of Fumed Silica on Thixotropic Behavior and Processing Window by UV-Assisted Direct Ink Writing - Jiang, Fengze; Zhou, Mingyong; Drummer, Dietmar (Polymers, 2022)
In this research, the effects of fumed silica (FS) on the Ultraviolet (UV)-ink rheological behavior and processing windows were discussed. Objects using different concentrations of FS inks were printed by the modified UV-Direct ink writing (DIW) printer. The function of fumed silica in the ink-based system has been verified, and the processing scope has been expended with a suitable amount of FS combined with the UV light. The results show that the combination of a suitable amount of FS with the UV-DIW system reaches fast and accurate printing with a larger processing window compared to the non-UV system. However, an excessively high concentration of FS will increase the yield stress of the ink, which also increases the requirement of extrusion unit and the die-swelling effects.
CRIS-Team WoS Importer:2022-08-26